1973
DOI: 10.1126/science.180.4090.1055
|View full text |Cite
|
Sign up to set email alerts
|

Monoclinic Hydroxyapatite

Abstract: The existence of a monoclinic phase of hydroxyapatite, Ca(2)(PO(4))(4)OH, has been confirmed, by single-crystal structure analysis (weighted "reliability" factor = 3.9 percent on |F|(2)). The structure has space group P21/b, a = 9.4214(8) angstroms, b = 2a, c = 6.8814(7) angstroms, and gamma = 120 degrees , and is analogous to that of chlorapatite. The distortions from the hexagonal structure with which the monoclinic structure is pseudosymmetric are similar to those in chlorapatite, including enlargement of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
228
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(239 citation statements)
references
References 11 publications
7
228
0
4
Order By: Relevance
“…The results per hexagonal cell are plotted in ascending energy order. The mixed configuration (↓↓)(↑↑) monoclinic structure suggested by Elliott [34], yields the lowest energy (structure 1) and is used as the reference energy. The lattice constants are a=9.53Å, b=2a and c=6.91Å.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results per hexagonal cell are plotted in ascending energy order. The mixed configuration (↓↓)(↑↑) monoclinic structure suggested by Elliott [34], yields the lowest energy (structure 1) and is used as the reference energy. The lattice constants are a=9.53Å, b=2a and c=6.91Å.…”
Section: Resultsmentioning
confidence: 99%
“…al. [34] who, following the work by Young [10], prepared a sample consisting of ~30% monoclinic HA and 70% hexagonal phases. They concluded that HA grown in a sufficiently clean experimental environment and having little impurities or vacancies can assume monoclinic symmetry under ambient conditions.…”
Section: B Activation Energy For the Hexagonal To Monoclinic Transitionmentioning
confidence: 99%
“…Citrate is needed to keep calcium in solution long enough (days) to inject into the subsurface because a solution containing Ca 2+ and phosphate only will rapidly form mono-and di-calcium phosphate, but not apatite (Andronescu et al 2002, Elliot et al 1973, Papargyris et al 2002. Relatively slow biodegradation of the Ca-citrate complex (days) allows sufficient time for the reagents to be injected and transported to the areas of the aquifer where treatment is required.…”
Section: Apatite Placement In the Subsurfacementioning
confidence: 99%
“…Citrate is needed to keep calcium in solution long enough (days) to inject into the subsurface; a solution containing Ca 2+ and phosphate only will rapidly form mono-and di-calcium phosphate, but not apatite (Andronescu et al 2002;Elliot et al 1973;Papargyris et al 2002). Relatively slow biodegradation of the Ca-citrate complex (days) allows sufficient time for injection and transport of the reagents to the areas of the aquifer where treatment is required.…”
Section: Apatite Placement In the Subsurfacementioning
confidence: 99%